When AI meets the audit - Kasim, Syazliana (Universiti Teknologi MARA Cawangan Negeri Sembilan Kampus Rembau, 2025)
Auditing has evolved from manual tools to a more advanced approach with the integration of Artificial Intelligence (AI), which helps auditors analyse large volumes of data, detect anomalies, and predict risks efficiently. While external auditors act as financial detectives ensuring accuracy and compliance in financial statements, AI enhances their work by quickly identifying patterns and flagging unusual transactions, making the auditing process faster and more effective.